Korelasi kemandirian belajar terhadap hasil belajar matematika siswa kelas V - Resmiyati Resmiyati; Mahmudah Titi Muanifah; Dewi Anggraeni; Trisniawati Trisniawati; Nelly Rhosyida (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study aims to: 1) Describe learning independence in mathematics learning of fifth-grade students at Cimpon Public Elementary School, Bantul Regency, Yogyakarta. 2) Describe learning outcomes in mathematics learning of fifth-grade students at Cimpon Public Elementary School, Bantul Regency, Yogyakarta. 3) Describe the correlation between learning independence and mathematics learning outcomes of fifth-grade students at Cimpon Public Elementary School, Bantul Regency, Yogyakarta. This type of research is quantitative, using an ex post facto research method, with a correlational research design. The study population was all fifth-grade students at Cimpon Public Elementary School, Bantul Regency, Yogyakarta, with a total of 14 students. Data collection techniques used questionnaires, tests, and documentation. Instrument measurement used construct validation and reliability testing. Prerequisite analysis tests included normality and linearity tests, and hypothesis testing using Pearson Product Moment. The results of this study are: 1) The average student learning independence was 100.57, which is categorized as moderate. 2) The average mathematics learning outcome was 80.21, which is categorized as very high. 3) Hypothesis testing based on the Pearson Correlation value of 0.427, indicating a moderate correlation between the variables and a positive coefficient. However, a significance value of 0.128 was obtained, as 0.128 > 0.05. Therefore, Ho is accepted, indicating that learning independence and mathematics learning outcomes are not correlated.